KUASA UPACARA REPRODUKSI DAN REKONSTRUKSI "SUKUR BUMI" DI RANCAKALONG SUMEDANG JAWA BARAT - , Yanti Heriyawati; , Prof. Dr. C. Sobakdi Soemanto, S.U., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The subject of this study is Sukur Bumi. It discusses power relation spreading in its reproduction and reconstruction form. The study is conducted on empirical data in tune with its inductive research. The method and theory are determined based on the practice. Sukur Bumi is a sacred ritual activity conducted by Rancakalong community as a gratitude expression for the harvest. The reproduction of Sukur Bumi is a ritual of progenitorâs inheritance done by the community hereditarily, while the reconstruction is a ritual reconstructed by the government with the community. The study on the reproduction symbols of Sukur Bumi uses structuralhermeneutic analysis. Meanwhile, discourse analysis is used to study the practice of Sukur Bumi in a reconstruction form. The whole study is conducted on the matters of power relations in the practice of reproduction and reconstruction of Sukur Bumi. The structural hermeneutic study on the ritual of ngalaksa, ngabubur, and the ritual as well as tarawangsa performance, shows that Sukur Bumi is the progenitorâs inheritance of Sunda Lama. The result of the analysis reveals âthe structure of threeâ which is the embodiment of Tritangtu Sunda concept. Meaning that, the one is three, and the tree is one. This concept clarifies the Sunda Lama ways of thinking in signifying life, that, this life is the unification of three different elements. Tritangtu also indicates a concept that Sunda power is distributed into three, meaning that the power is not centralized, since âthe ownerâ of the power is not functioned as âthe executorâ or âthe one running the orderâ. The reconstruction model of Sukur Bumi is the changing form of the execution of the ritual, although the changing is on the surface level. However, this condition becomes a strategic sphere for the government in constructing its political economy discourse. The discourse has relation with tourism matters so that there is an emergence of commodification which position Sukur Bumi as a cultural asset having selling values. Besides, it also has relation with the construction of governmental power toward the people. The resistance of the community on the ritual performance is that it can only be conducted by the community not by any other parties. Meanwhile, the tourism field can be signified by the society as social interaction sphere, which contributes to promote creative ideas for developing and conserving cultural values. Power is not understood as hierarchical or centralized relation, but distributed. The power relation between the progenitor and the society